Automated Technology for Verification and Analysis 9th International Symposium, ATVA 2011, Taipei, Taiwan, October 11-14, 2011. Proceedings - Bultan, Tevfik; Hsiung, Pao-Ann.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 9th International Symposium on Automated Technology for Verification and Analysis, ATVA 2011, held in Taipei, Taiwan, in October 2011. The 23 revised regular papers presented together with 5 invited papers, 11 short papers, and 2 tool papers, were carefully reviewed and selected from 75 submissions. The papers address all theoretical and practical aspects of automated analysis, verification and synthesis; thus providing a forum for interaction between the regional and the international research communities and industry in the field.
Keywords: Computer science; Computer Communication Networks; Software engineering; Logic design; Computer Science; Software Engineering; Programming Techniques; Computer Communication Networks; Logics and Meanings of Programs; Programming Languages, Compilers, Interpreters; Software Engineering/Programming and Operating Systems